2022
DOI: 10.1002/app.53383
|View full text |Cite
|
Sign up to set email alerts
|

Polymer electrolyte membrane modification in direct ethanol fuel cells: An update

Abstract: Direct ethanol fuel cells (DEFCs) offer a high degree of design flexibility, ranging from a single cell to a massive multi‐cell that can be used in various applications, including portable devices, transportation, and stationary applications. Unfortunately, the most significant barrier to the commercialization of DEFCs is getting low‐cost and ethanol permeability, high conductivity performance, and extended durability of polymer electrolyte membranes, as key components that highly influence the overall perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 122 publications
0
9
0
Order By: Relevance
“…Moreover, PVA can be simply modified by introducing other functional groups, making it a versatile material for gel-polymer electrolyte applications [ 25 ]. The functional groups of PVA-based electrolytes can be conveniently adjusted using various physical and chemical techniques, including plasma treatment [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PVA can be simply modified by introducing other functional groups, making it a versatile material for gel-polymer electrolyte applications [ 25 ]. The functional groups of PVA-based electrolytes can be conveniently adjusted using various physical and chemical techniques, including plasma treatment [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, when the membrane is applied in a direct liquid fuel cell such as DEFC, fuel crossover problems have led to a decline in the single-cell performance of DEFC. [12][13][14] Therefore, our previous research has developed a filler from chicken eggshell material and used it in Nafion for direct methanol fuel cells (DMFC). 15 We found that chicken eggshells' main ingredient/compound is calcium carbonate (CaCO 3 ), and other researchers also support this finding.…”
Section: Introductionmentioning
confidence: 99%
“…Nafion membranes are commonly used in fuel cells because of their high proton conductivity. However, when the membrane is applied in a direct liquid fuel cell such as DEFC, fuel crossover problems have led to a decline in the single‐cell performance of DEFC 12‐14 . Therefore, our previous research has developed a filler from chicken eggshell material and used it in Nafion for direct methanol fuel cells (DMFC) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Among sustainable biofuels, ethanol is the most commonly adopted option worldwide, and as a renewable source, it offers zero net emissions . This is due to ethanol being economically viable, , easy to produce, and non-toxic, and it can be obtained from various crops and vegetable waste. , Additionally, instead of being burned, ethanol can be converted straight to electricity using ethanol-based fuel cells, based on research conducted to improve the efficiency of such devices. , …”
Section: Introductionmentioning
confidence: 99%